2017
DOI: 10.1186/s12889-017-4838-y
|View full text |Cite
|
Sign up to set email alerts
|

From action planning and plan enactment to fruit consumption: moderated mediation effects

Abstract: ObjectivesSufficient fruit consumption is beneficial for a healthy live. While many Dutch adults intent to eat the recommended amount of fruit, only 5–10% of the population actually adheres to the recommendation. One mechanism that can help to narrow this gap between intention and actual fruit consumption is action planning. However, action planning is only assumed to be effective if plans are enacted. This study assessed which action plans are made and enacted, and further aimed to investigate two main hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 62 publications
1
7
1
Order By: Relevance
“…Gholami et al also showed that eating habits had the greatest impact on F&V intake ( 34 ) . In the present study, the reliability coefficient of this construct was 0·85, which was optimal; however, it was lower than that of the Gholami (0·90) and Kasten (0·95) studies ( 19 , 28 ) . Other models and theories have also been applied to develop instruments regarding the predictors of F&V intake such as the theory of planned behaviour and the stages of change model.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Gholami et al also showed that eating habits had the greatest impact on F&V intake ( 34 ) . In the present study, the reliability coefficient of this construct was 0·85, which was optimal; however, it was lower than that of the Gholami (0·90) and Kasten (0·95) studies ( 19 , 28 ) . Other models and theories have also been applied to develop instruments regarding the predictors of F&V intake such as the theory of planned behaviour and the stages of change model.…”
Section: Discussioncontrasting
confidence: 73%
“…Thus, studies conducted in recent decades have focused mainly on perception of generation and maintenance of healthy behaviour ( 17 ) . The identification of mediation factors has an effective role in formulating intervention programmes ( 19 ) . One of such factors is to attract social support for healthy nutrition, which can be attributed to the positive effect and encouragement of others to have healthy eating habits ( 20 ) .…”
Section: Introductionmentioning
confidence: 99%
“…[ 14 ] In this regard, it is very important to develop programs with an emphasis on the need to consider the facilitators of consuming F and V. The findings of Kasten et al in the Netherlands showed that high levels of intention and self-efficacy as well as strong habits of consuming F and V clearly help to develop action plans. [ 15 ] In the meantime, models and theories can be used as a guide to discover health-related processes[ 16 ] and identify the factors affecting the adoption of health-oriented behaviors (e.g., attitudes, norms, self-efficacy, environmental or social considerations, or a combination of them) to plan and develop appropriate interventions. [ 17 ] Since theories and models increase productivity and effectiveness by eliminating inappropriate factors and focusing on the most important issues, theory-based interventions are more effective than those that are not developed based on scientific theories.…”
Section: Introductionmentioning
confidence: 99%
“…Research has, for instance, shown that factors such as knowledge and risk perceptions may play an important role as factors determining motivational factors such as attitudes and self-efficacy (45). Additionally, only a limited amount of the variance of behavior is explained by intention, and therefore the role of developing and enacting action plans should be addressed in order to understand and change behavior (46)(47)(48)(49)(50).…”
Section: Understanding Adherence To Healthy Lifestyle and Medical Behmentioning
confidence: 99%
“…on how to anticipate low self-efficacious situations, on what goals are feasible and realistic, and on how to prepare an intended behavior. Such factors -also referred to as action plans -are likely to facilitate enactment of intentions, and could yield information to be addressed in interventions (56), and have been shown to increase the chance of translating intentions into the desired goal behavior (46,49,50). Consequently, these factors were addressed in our intervention.…”
Section: Determinants Of Treatment Adherencementioning
confidence: 99%